Association between spirituality, religiosity & religious coping with oral medication adherence amongst schizophrenia patients in a Malaysian community setting / Ian Llyoyd Anthony - Ian Llyoyd, Anthony (2013)
Introduction: Schizophrenia is a chronic debilitating mental disorder. Recent research has shown that schizophrenic patients tend to turn to religion and spirituality to help them cope with their illness. Religiosity and spirituality also appears to improve antipsychotic medication adherence, a problem that is inherent in schizophrenia. Objective: The aim of this study is to examine the prevalence of religiosity and spirituality amongst schizophrenic patients, the associated socio-demographic and clinical factors as well as to determine its relationship with medication adherence. Methodology: This is a cross-sectional study involving 153 schizophrenic patients who are enrolled in the Assertive Community Treatment programme of Hospital Bahagia Ulu Kinta. The diagnosis of schizophrenia was confirmed using M.I.N.I. The PANSS was used to screen for stable patients and the Yangarber-Hicks criteria was used to exclude religious delusions. Patients who fulfilled the inclusion criteria were assessed for religious commitment, spirituality and religious coping using the DUREL, Spiritual Well-Being Scale and Brief RCOPE respectively. Medication adherence and insight were assessed using the BARS and SUMD. Results: The prevalence of religiosity, spirituality and positive religious coping were 52.9%, 50.8% and 50.0% respectively. Muslim (OR=1.912, p=0.048) and Hindu (OR=3.720, p=0.039) patients were found to be more religious than the Buddhists. Muslim patients also had positive religious coping (OR=1.996, p=0.042) while Buddhist patients had lower odds of positive coping (OR=0.404, p=0.014). Hindu patients were more spiritual than the Muslims and Buddhists (OR 7.840, p=0.048). Employment was found to be significantly associated with religiosity and religious coping. Religiosity, spirituality and religious coping were all significantly correlated with medication adherence and insight (p<0.001). Conclusion: Religion and spirituality were found to be central in the lives of schizophrenic patients and the majority of them used it to cope positively with their illness. Those who were religious, spiritual and practised positive religious coping had better insight and were more adherent to their medication. Further studies should be done to determine the stability of religion and spirituality as a coping mechanism and its long term influence on the sustenance of medication adherence amongst schizophrenic patients.